Post-HIPC growth dynamics in Sub-Saharan Africa - Bayraktar, Nihal; Fofack, Hippolyte (2012)
Access to debt relief under the Highly Indebted Poor Country Initiative enhanced the growth performance across Sub-Saharan Africa, especially in the subset of debt-ridden low-income countries. Over the past few years, these Completion Point countries have enjoyed significantly higher investments and growth rates, primarily fueled by the expanding fiscal space of the post-Highly Indebted Poor Country Initiative era. They are also weathering the adverse effects of the global crisis much better than their non-Highly Indebted Poor Country Initiative counterparts. Despite these growth rebounds, the region is not likely to meet the Millennium Development Goals, however. Long-term growth projections from a simple macroeconomic model, which is applied to Ethiopia, suggest that prospects for reversing the widening income gaps with other regions of the developing world are limited. Under the baseline scenario, assuming current growth trends, the estimates show that it could take more than five decades for per capita real income to double in Ethiopia. However, even these gloomy prospects are likely to be undermined by the looming risk of another sovereign debt crisis. In effect, the experiments show that lowering interest rates on external debt would not bridge the widening income gap with other regions of the world, unless it is accompanied by a rapid expansion of capital accumulation financed by sustained inflows of foreign aid.